Alterações da linguagem escrita no processo de alfabetização no município de Cajati/SP - Almeida, Gleide Viviani Maciel (2013)
The teachers are frequently sending their students to a speech therapist treatment because of the complaints of learning, but they rarely consider the lack of stimulation and/or the methodology failure as being the cause of the students´ low performance. The overall goal is to characterize the major alterations in learning existent in the students. The specific goals is characterized, from the answers provided by the teachers, changes in learning that judge be present in students and identify complaints regarding written frequently detected by teachers. Methodology: this research is a transverse sectional quantitative individuated study. 21 teachers from the literacy cycle (from the 1st to the 3rd school year) who work at public schools have participated in this study, 7 from de first year, 6 from the second year and 8 from the third year. Those groups were divided into 2 subgroups: G1 – early literacy (1st and 2nd school year) and G2 – end of the literacy (3rd school year). A formulated questionnaire was answered by the teachers. Fisher´s test was used as a statistic instrument. By the finding, there was a significant difference in the historical changes proportion of language before schooling, being bigger in the final school year. According to the year attended, the facility in the text comprehension was greater among younger students. Regarding the ability to express ideas through writing the proportion of students is bigger among those that studies in the afternoon. Concluding that the delay in the acquisition of the language can damage the process of literacy what includes the pragmatic ability and expressive function.